ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT BASED ON MAQASHID SYARIAH IN REALIZING THE WELFARE OF THE PEOPLE - Layli, Jumbratul; Muchlis, Saiful; Jannah, Raodahtul Odha (Islamic Economic and Business Journal, 2025)
This study aims to analyze the implementation of the principle of accountability in the management of village funds based on maqashid sharia in Pattallassang Village, Gowa Regency. This study uses a qualitative method with a phenomenological approach. The results of the study indicate that the management of village funds in Pattallassang Village has shown good implementation of the principles of transparency, accountability, and community participation. The application of the principle of maqashid sharia is also seen in programs that support religious activities, health, and community welfare. However, there are still challenges related to the understanding of village officials regarding the concept of maqashid sharia and limitations in preparing targeted programs. This study recommends increasing the capacity of village officials and multi-party collaboration to optimize the management of village funds and improve community welfare.